Mutation of HPR1 encoding a component of the THO/TREX complex reduces STOP1 accumulation and aluminium resistance in Arabidopsis thaliana. Issue 1 (11th June 2020) - Guo, Jinliang; Zhang, Yang; Gao, Huiling; Li, Shengben; Wang, Zhen‐Yu; Huang, Chao‐Feng
Summary: C2H2‐type zinc finger transcription factor sensitive to proton rhizotoxicity 1 (STOP1) plays an essential role in aluminium (Al) resistance in Arabidopsis thaliana by controlling the expression of a set of Al‐resistance genes, including the malate transporter‐encoding gene A. thaliana aluminium activated malate transporter 1 ( AtALMT1 ) that is critically required for Al resistance. STOP1 is suggested to be modulated by Al at post‐transcriptional and/or post‐translational levels. However, the underlying molecular mechanisms remain to be demonstrated. We carried out a forward genetic screen on an ethyl methanesulphonate mutagenized population, which contains the AtALMT1 promoter‐driven luciferase reporter gene ( pAtALMT1:LUC ), and identified hyperrecombination protein 1 ( HPR1 ), which encodes a subunit of the THO/TREX complex. We investigate the effect of hpr1 mutations on the expression of Al‐resistance genes and Al resistance, and we also examined the regulatory role of HPR1 in nuclear messenger RNA (mRNA) and protein accumulation of STOP1 gene. Mutation of HPR1 reduces the expression of STOP1‐regulated genes and the associated Al resistance. The hpr1 mutations increase STOP1 mRNA retention in the nucleus and consequently decrease STOP1 protein abundance. Mutation of regulation of AtALMT1 expression 1 ( RAE1 ) that mediates STOP1 degradation in the hpr1 mutant background can partially rescue the deficient phenotypes of hpr1 mutants. Our results demonstrate that HPR1 modulates Al resistance partly through the regulation of nucleocytoplasmic STOP1 mRNA export.